Saline–Alkali Tolerance Evaluation of Giant Reed (Arundo donax) Genotypes Under Saline–Alkali Stress at Seedling Stage - Yangxing Cai; Xiuming Cao; Bin Liu; Hui Lin; Hailing Luo; Fengshan Liu; Dewei Su; Shi Lv; Zhanxi Lin; Dongmei Lin (Agronomy)
Soil salinization and alkalization are serious global challenges that adversely affect crop growth and yield. In this study, six genotypes of giant reed (Arundo donax) seedlings (LvZhou_No.1, LvZhou_No.3, LvZhou_No.6, LvZhou_No.11, LvZhou_No.12 and LvZhou_Var.) originating from different regions of China and Rwanda were utilized as experimental materials. This study aimed to investigate the physiological and biochemical responses of various genotypes to saline–alkali stress and to identify stress-tolerant resources. A mixture saline–alkali solution with a molar ratio of NaCl: Na2SO4: NaHCO3: Na2CO3 = 1:1:1:1 was prepared at three concentrations (75, 150 and 225 millimolar (mM)) for a 7-day pot experiment. Growth and physiological indices were measured at the seedling stage, and salt tolerance was evaluated accordingly. The results indicated the following: the growth indices were significantly reduced across seedlings of all genotypes when the concentration of stress exceeded 150 mM (p < 0.05). There was no significant difference in chlorophyll content (SPAD value) and maximum photochemical efficiency of PS II (Fv/Fm) with increasing saline–alkali stress. However, the photosynthetic rate (Pn), stomatal conductance (Gs) and transpiration rate (Tr) exhibited decreasing trends, reaching their lowest levels at 225 mM. In contrast, the intercellular CO2 concentration (Ci) value decreased to its lowest at 150 mM but increased at 225 mM. Relative electrical conductivity (REC) and the contents of malondialdehyde (MDA), proline (Pro) and soluble sugar (SS) increased progressively with higher stress concentrations. The activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) were significantly enhanced at stress concentrations above 150 mM. The saline–alkali tolerance of A. donax seedlings was comprehensively evaluated using principal component analysis and membership function analysis based on 15 parameters. The results indicate that Pn, Tr and Gs are effective physiological indicators for assessing saline–alkali tolerance of A. donax seedlings. The six genotypes were ranked for saline–alkali tolerance as follows: LZ_No.1 > LZ_No.11 > LZ_No.12 > LZ_Var. > LZ_No.3 > LZ_No.6. This indicates that LZ_No.1 shows the highest resistance to saline–alkali stress, whereas LZ_No.6 is the most severely affected, classifying it as a salinity-sensitive genotype. In conclusion, LZ_No.1 exhibits robust saline–alkali tolerance and represents a valuable germplasm resource for improving saline–alkali tolerance in A. donax propagation. The results not only support the development of resilient plants for saline–alkali environments but also offer insights into the mechanisms of salinity tolerance.